Penerapan Bahasa Jurnalistik Radio pada Berita Ekonomi dalam Program “Halo Bharabas” di Radio Bharabas FM Pekanbaru - Monika, Dinda; Wahidar, Tutut Ismi (Yayasan Lentera Avanya Nagari, 2024)
Using language in journalism is very important. This research aims to find out how journalistic language is applied in the